(x/x-y+2xy/x^2-2xy+y^2)*(2x/x+y-1) при x= -2; y= -1 /-дробь ^-степень *-умножить

Каримончик Каримончик    1   21.09.2019 17:50    0

Ответы
ninahatsanowsk ninahatsanowsk  08.10.2020 07:45
.........=(\frac{x}{x-y} + \frac{2xy}{(x-y)(x-y)} )* (\frac{2x}{x+y} -1)= \frac{x(x-y)+2xy}{(x-y)(x-y)} * \frac{2x-x-y}{x+y}= \\ \\ \frac{ x^{2} -xy+2xy}{(x-y)(x-y)} * \frac{x-y}{x+y} = \frac{ x^{2} +xy}{(x-y)(x-y)} *\frac{x-y}{x+y}= \frac{x(x+y)}{(x-y)(x-y)}* \frac{x-y}{x+y}= \\ \\ \frac{x}{x-y}

при  х= -2, у= -1

\frac{-2}{-2-(-1)}= \frac{-2}{-2+1} = \frac{-2}{-1} =2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра